2019
DOI: 10.12965/jer.1938314.157
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effects of foam roller with vibration on hamstring flexibility and jump performance in healthy adults

Abstract: Ahmed S and Akte R • Letter to the editor: effects of foam roller vibration t-test and analysis of covariance those are parametric tests that are not appropriate for this statistical analysis.Other than the aforesaid issue, this current study can helps the fellow clinician, athletes and population who are used to foam roller. We congratulate the authors for their valuable research and we would recommend that the authors revise their methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…Hip extension ROM increased in the VFR group only, while MVIC peak torque increased and shear modulus of the RF decreased in both groups (VFR, NVFR). As in the current study, a superior effect for the increase in ROM following a single bout of foam rolling with VFR compared to NVFR was reported by Lim and Park (2019) and Lee et al (2018) but not by other studies (Sağiroğlui 2017;Cheatham and Stull 2018;Lee et al 2018;de Benito et al 2019). A possible explanation for a greater ROM in VFR compared to NFVR might be found in a more advanced decrease in perception of pain (i.e.…”
Section: Discussioncontrasting
confidence: 61%
“…Hip extension ROM increased in the VFR group only, while MVIC peak torque increased and shear modulus of the RF decreased in both groups (VFR, NVFR). As in the current study, a superior effect for the increase in ROM following a single bout of foam rolling with VFR compared to NVFR was reported by Lim and Park (2019) and Lee et al (2018) but not by other studies (Sağiroğlui 2017;Cheatham and Stull 2018;Lee et al 2018;de Benito et al 2019). A possible explanation for a greater ROM in VFR compared to NFVR might be found in a more advanced decrease in perception of pain (i.e.…”
Section: Discussioncontrasting
confidence: 61%
“…Hamstring shortening is further characterized by altered muscle recruitment patterns, as well as decreased strength [ 13 ]. It has been shown that, when hamstring flexibility is improved, the maximum concentric and eccentric strength are also increased [ 14 ]. And, in this sense, improvements in muscle strength are recommended to prepare the athletes to sustain the high work rates throughout training and matches and mitigate their injury risk [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of soft-tissue release techniques seems to prevent those dysfunctions without strength impairment [ 9 , 19 ]. Different soft tissue mobilizations techniques have been studied before in order to evaluate athletic performance effects in athletes [ 12 , 14 , 15 ]. It has also been reported that manual techniques could increase blood flow and temperature but also normalize muscle activity.…”
Section: Introductionmentioning
confidence: 99%